Prevalence and pattern of impacted mandibular third molar: An institution-based retrospective study - Sundarrajan KalaiSelvan; Sappaniapillai Kathiresan Nithya Ganesh; Pughalaendhi Natesh; Murugesan Senthil Moorthy; Thanvir Mohamed Niazi; Sitharaju Santhosh Babu (Wolters Kluwer Medknow Publications, 2020)
Introduction: The third molar is the most frequently impacted tooth with a frequency of occurrence generally reported to be from 18 to 32%. It is considered impacted when its eruption into normal functional occlusion has been interfered with by other teeth, overlying bone or soft tissue and when it is not fully erupted by its expected age of around 20 years. Racial differences affect the pattern of impaction. There is a lacunae of literature on the pattern of mandibular third molar impaction in Tamil population. Aim: To investigate the prevalence of pattern of third molar impaction among the population in Madurai. Materials and Methods: A retrospective cohort study was conducted. The first 1000 OPGs (Orthopantamograms) were taken at the Department of Oral Medicine and Radiology, CSI College of Dental Sciences and Research from August to December 2018 of Madurai population aged between 20 and 40 years old. Data include angle, level and position of impaction, proximity to inferior alveolar nerve and dental caries in second molar and/or third molar. Results: The average age of subject with mandibular third molar impaction is 30.5 years. The most common occurring mandibular impaction is mesioanglar (60%), Level A (71%), Class II (50%) without involving the inferior alveolar nerve (33%) and dental caries in 20% of second and/ or third molar. Conclusion: Mandibular third molar impactions are one of the common developmental condition in this modern civilization. Assessing the third molar and prognosis of its eruption is mandatory for better patient management because of numerous complications associated with unerupted third molar.